2018
DOI: 10.1021/acs.jmedchem.7b01353
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Exploration of Macrocyclization in Apelin-13: Impact on Binding, Signaling, Stability, and Cardiovascular Effects

Abstract: The apelin receptor generates increasing interest as a potential target across several cardiovascular indications. However, the short half-life of its cognate ligands, the apelin peptides, is a limiting factor for pharmacological use. In this study, we systematically explored each position of apelin-13 to find the best position to cyclize the peptide, with the goal to improve its stability while optimizing its binding affinity and signaling profile. Macrocyclic analogues showed a remarkably higher stability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 66 publications
1
41
0
3
Order By: Relevance
“…This study underlines the possible link between G protein‐independent signaling and hypotensive effect in the apelinergic system . More recently, a rolling loop scan study conducted on apelin‐13 led to the identification of KT01–3 ( 31 ) (Figure F) bridged on the C ‐terminal region of the peptide . 31 exhibits similar affinity compared to the endogenous ligand ( K i 1.1 nM) and is 10‐fold less potent on Gα i1 activation (EC 50 19 nM) and β‐arrestin‐2 recruitment (EC 50 272 nM).…”
Section: Structure–activity Relationship Of Apelin‐13mentioning
confidence: 60%
“…This study underlines the possible link between G protein‐independent signaling and hypotensive effect in the apelinergic system . More recently, a rolling loop scan study conducted on apelin‐13 led to the identification of KT01–3 ( 31 ) (Figure F) bridged on the C ‐terminal region of the peptide . 31 exhibits similar affinity compared to the endogenous ligand ( K i 1.1 nM) and is 10‐fold less potent on Gα i1 activation (EC 50 19 nM) and β‐arrestin‐2 recruitment (EC 50 272 nM).…”
Section: Structure–activity Relationship Of Apelin‐13mentioning
confidence: 60%
“…A further systematic study of macrocyclization in Pyr 1 ‐apelin‐13 identified the N‐ and C‐termini as preferable sites for cyclization to retain good binding and signaling properties, and to significantly increase plasma stability. In this series, low nM, G αi ‐biased agonists were identified, and they demonstrated, as suggested above, very low hypotensive properties in rats in vivo , as well as strong inotropic properties in the Langendorff isolated perfused heart model …”
Section: Toward Pharmacological Probes and Novel Drugsmentioning
confidence: 64%
“…Moreover, KKS has been described as a specific node linking the inflammatory and coagulation responses to microbial infection and thus contributing to the pathogenesis of sepsis 42 . The biological efficiency of the apelin system is therefore compromised under this environmental pressure, given the very short half-lives of endogenous APLNs 43 . Accordingly, a PCA of this cohort revealed that nonsurvivors were widely located within a component corresponding to enhanced apelinergic release-degradation system activity.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive radioligand binding experiments were performed as previously described 43 using [ 125 I]-(pyr 1 )Apelin(APLN)-13 (820 Ci/mmol) prepared with IODO-GEN (1,3,4,6-tetrachloro-3a,6a-diphenyl-glycoluril; Thermo Scientific Pierce, Canada) 49 . In brief, HEK293 cells with surface expression of HA epitope-tagged sheep APJ generated as previously described (ref Murza) were incubated with 0.2 nM radiolabeled APLN-13 and increasing concentrations of cold APLN-13 or ELA synthesized as previously described 50 (10 –11 to 10 –5 M) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation